Optimal Community Assembly Related to Leaf Economic- Hydraulic-Anatomical Traits - Liu, Congcong; Li, Ying; Zhang, Jiahui; Baird, Alec S.; He, Nianpeng (Frontiers in Plant Science, 2020)
Multi-dimensional trait mechanisms underlying community assembly at regional scales are largely unclear. In this study, we measured leaf economic, hydraulic and anatomical traits of 394 tree species from tropical to cold temperate forests, from which we calculated the leaf trait moments (mean, variance, skewness, and kurtosis) using community-weighted methods. Economic and hydraulic traits were decoupled at the species level, but coupled at the community level, and relationships between leaf traits in observed communities were stronger than that in null communities, suggesting that the adaptive mechanisms of plant species may be different. Furthermore, leaf economic traits were distributed more evenly across species occupying communities with lower temperature and precipitation, whereas hydraulic traits were distributed more evenly under lower water availability. This suggests that limiting similarity of specific leaf traits within communities would be enhanced when related-resources are limited, and highlights the independent assembly of leaf economics and hydraulic traits in terms of functional evenness. Importantly, the moments of leaf economic and hydraulic traits of observed communities explained more variation in ecosystem productivity than that of null communities, indicating ecosystem productivity depended on trait-based community assembly. Our results highlight the principles of community assembly regarding multi-dimensionsional traits in natural forests at a regional scale.